(untitled) - Pauw, De N. (Belgium, 1996)
Contents: Biological monitoring of river quality; sampling of macro-invertabrates; identification of macro-invertebrates.
Keywords: Water quality biological assessment.,Freshwater invertebrates,Chất lượng nước